Potential for Science Laboratory Development: A SWOT Analysis - Aisyah; Siregar, Fadly Shalsabil; Utami, Wiji; Primarani, Nabila Risa; Setyawati, Ria (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
The laboratory is inseparable from the learning process at the Faculty of Science and Technology. Therefore, it is important to have quality standards that are a benchmark and reference in laboratory work. These quality standards include laboratory buildings/rooms, quality control, facilities and equipment, risk management, and waste disposal. Laboratories that comply with these standards have great potential to grow. This study aims to identify strategies to implement in the management and development of the Faculty of Science and Technology laboratories. This study uses a SWOT analysis method through a qualitative approach obtained from interviews with laboratory heads and workers. The SWOT analysis results show that the FST laboratory is in quadrant I, where strengths and opportunities can be utilized. The results of IFE internal factors and EFE external factors obtained a strength and opportunities (SO) value of 3.75, strength and threats (ST) of 3.55, weakness and opportunities (WO) of 3.64; and weakness and threats (WT) of 3.44 indicate a fairly good position. The data from this research can be used as a reference in designing the formulation of the right strategy for developing the Faculty of Science and Technology laboratory. The latest research significantly contributes to the potential development of science laboratories at the university level under the Ministry of Religion.